The Effect Of Health, Education, Capital, Technology, Inflation, And Gross Of Regional Domestic Products On Poverty Level In North Maluku Province - Tommy Kuncara; Didin Mukodim; Waseso Segoro (Publisher Cv. Inara, 2021)
Poverty is a social problem that occurs due to various factors including economic, social and cultural. This problem continues to occur in almost every developing country and the same case is also found in countries that are already advanced in their economic systems. Currently in Indonesia, especially the problem of poverty is still concentrated in the eastern part of Indonesia, this is caused by uneven human development in terms of education, employment, infrastructure, and the economy. The purpose of this study is to analyze the effect of labor on the poverty level, the effect of capital on the poverty level, the effect of inflation on the poverty level, and the effect of gross regional domestic product on the poverty level. The object of research is the Province North Maluku. The data used in this research is secondary data. The data analysis method uses a panel data regression model with an estimated random effect model and a fixed effect model. Then the analysis technique used is the determination of the panel data estimation model, the classical assumption test, and the significance test. The results of this study indicate that the variable life expectancy which represents overall health has no effect on the level of poor people in North Maluku Province. The variable of Old School Expectation which represents education in general affects the level of poor people in does not affect the poverty level in North Maluku Province. The variable average length of schooling represents education in general that affects the level of the poor in North Maluku Province. Capital is divided into Capital Expenditure variables and KUR represents Capital. Capital Expenditure as a whole has an effect on the poverty level has no effect on the poverty level in North Maluku Province. KUR as a whole does not affect the poverty level does not affect the poverty level in North Maluku Province. The technology variable that represents technology as a whole affects the poverty rate does not affect the poverty rate in North Maluku Province. Inflation variable is inflation as a whole does not affect the poverty level also in North Maluku Province. The Gross Regional Domestic Product (GRDP) variable represents the overall GRDP that affects the poverty level does not affect the poverty level in North Maluku Province.